2014
DOI: 10.1136/emermed-2013-203073
|View full text |Cite
|
Sign up to set email alerts
|

Fascia iliaca block for pain relief from proximal femoral fracture in the emergency department: a review of the literature

Abstract: the fascia iliaca block could have an important role in first-line pain control for patients presenting to the emergency department with a proximal femoral fracture. There is potential to reform the acute management of this common group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Chesters and Atkinson recently published a systematic review of the efficacy of FICB (Chesters and Atkinson, 2014), but their review only considered 2 randomised control trial papers. One of these, by Foss et al (2007), is described as a 'placebo controlled trial'.…”
Section: Resultsmentioning
confidence: 98%
“…Chesters and Atkinson recently published a systematic review of the efficacy of FICB (Chesters and Atkinson, 2014), but their review only considered 2 randomised control trial papers. One of these, by Foss et al (2007), is described as a 'placebo controlled trial'.…”
Section: Resultsmentioning
confidence: 98%
“…With growing evidence that this is a safe, quick and easy to insert block , FIBs are gaining popularity and becoming widely used for peri‐operative pain relief in acute hip fracture, as seen by the increasing use of FIBs in the literature over the last decade . The FIB has been found to be comparable in effectiveness to older blocks such as the ‘3‐in‐1’ femoral nerve block , with now sufficient evidence to support that FIB can provide superior or equal pain relief to other forms of acute analgesia .…”
Section: Methodsmentioning
confidence: 95%
“…The use of local anesthetic nerve block has been recommended by the UK National Institute of Health and Care Excellence as part of an opioid sparing strategy. [26] Currently, FNB versus FIB in reducing opioids consumption remains controversial. Newman et al [27] reported that patients with femoral neck fracture receiving a FNB required less morphine after the block than those receiving fascia iliaca compartment block.…”
Section: Discussionmentioning
confidence: 99%